1983
DOI: 10.1111/j.1748-1716.1983.tb07234.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired medullary circulation in postischemic acute renal failure

Abstract: Acute renal failure was induced in heparinized rats by clamping the renal artery for 45 min. Ten minutes after recirculation the intrarenal blood flow distribution was measured. For this purpose labelled microspheres were injected together with 86-Rb chloride. The microspheres were used for determination of cardiac output, total renal and cortical blood flow, and 86-Rb for calculations of medullary blood flow. Total renal blood flow was reduced from 7.6 to 3.8 ml . min-1 . g-1 and cortical blood flow was reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 25 publications
3
50
0
Order By: Relevance
“…This observation could reflect the lower postischemic medullary blood flow, which has been attributed to characteristic dysfunctions in acute renal failure (11). The c-Kitϩ/CM-Dilϩ cells had apparently not significantly incorporated into the walls of small vessels.…”
Section: Discussionmentioning
confidence: 94%
“…This observation could reflect the lower postischemic medullary blood flow, which has been attributed to characteristic dysfunctions in acute renal failure (11). The c-Kitϩ/CM-Dilϩ cells had apparently not significantly incorporated into the walls of small vessels.…”
Section: Discussionmentioning
confidence: 94%
“…The decrease in GFR after renal ischemia/reperfusion is associated with an increased production of endothelin and reactive oxygen species, which may be responsible for increasing renal vascular resistance after ischemia/reperfusion (34,35). One of the most sensitive regions of the kidney to alterations in blood flow after ischemia is the medullary circulation (36,37). Recent studies have demonstrated that CO is endogenously produced in this region of the kidney and that this locally produced CO plays an important role in the regulation of medullary blood flow (38).…”
Section: Discussionmentioning
confidence: 99%
“…Of greater importance are the regional alterations in RBF that occur during AKI (13). Blood flow to the outer medulla is reduced disproportionately to the reduction in total kidney perfusion in animal models of AKI (17,18) and likely in humans following ischemic injury to the kidney. Endothelial cells are important determinants of vascular tone, leukocyte function, and smooth muscle responsiveness (19).…”
Section: Endothelium and Vascular Components Of Injurymentioning
confidence: 99%